Gonorrhoea treatment guideline compliance and influence factors in Guangdong province, China: a cross-sectional survey - Xiong, Mingzhou; Zhao, Peizhen; Wu, Xingzhong; Huang, Shujie; Yang, Menglan; Wang, Cheng; Zheng, Heping (BMJ open, 2024)
BackgroundThe indiscriminate use of antibiotics has accelerated antimicrobial resistance (AMR) in Neisseria gonorrhoeae (NG), emphasising the need to follow treatment guidelines. This study aimed to assess the rate of adherence to standard treatment among patients with gonorrhoea and identify influencing factors.MethodsA survey was conducted in Guangdong province, China, involving uncomplicated gonorrhoea cases registered in the Chinese Information System for Disease Control and Prevention. Data on demographic characteristics and medical information were collected to determine the standard treatment rate, defined as the proportion of patients receiving treatment according to national guidelines (ie, a single dose of ceftriaxone 250 mg, spectinomycin 2 g, cefotaxime 1 g or other third-generation cephalosporins). Medication choices were documented. χ² tests and multilevel logistic regression were used to analyse factors associated with standard treatment.ResultsThe survey included 2424 patients with gonorrhoea from 59 hospitals. The standard treatment rate was 30.7% (743/2424), with 36.2% for females and 29.6% for males. Common reasons for substandard treatment included the use of non-guideline medications (42.3%, 710/1681) and incorrect dosing (36.2%, 605/1681). Factors associated with the standard treatment rate included gender, address, educational level, department, physicians’ training, number of diagnosed gonorrhoea cases and hospital level.ConclusionThe standard treatment rate for gonorrhoea in Guangdong province, China, is below expectations. Comprehensive measures, such as establishing a goal-directed monitoring system and implementing promotional activities, are needed to improve adherence to treatment guidelines.